2017
DOI: 10.1111/epi.13802
|View full text |Cite
|
Sign up to set email alerts
|

Serum protein binding of 25 antiepileptic drugs in a routine clinical setting: A comparison of free non–protein‐bound concentrations

Abstract: These data provide a comprehensive comparison of serum protein binding of all available AEDs including the metabolites, carbamazepine-epoxide and N-desmethyl-clobazam. Knowledge of the free fraction of these AEDs can be used to optimize epilepsy treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
97
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(106 citation statements)
references
References 36 publications
0
97
0
Order By: Relevance
“…The L‐amino acid transport system 2 (LAT2) activity is involved in GAB absorption and the saturation of the transporter explains the dose‐dependent oral bioavailability . GAB does not bind to plasma proteins, is not metabolised and is eliminated unchanged in urine . Renal function showed a positive correlation with GAB renal clearance, since GAB is mainly eliminated by glomerular filtration .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The L‐amino acid transport system 2 (LAT2) activity is involved in GAB absorption and the saturation of the transporter explains the dose‐dependent oral bioavailability . GAB does not bind to plasma proteins, is not metabolised and is eliminated unchanged in urine . Renal function showed a positive correlation with GAB renal clearance, since GAB is mainly eliminated by glomerular filtration .…”
Section: Introductionmentioning
confidence: 99%
“…8,[11][12][13][14] GAB does not bind to plasma proteins, is not metabolised and is eliminated unchanged in urine. [15][16][17] Renal function showed a positive correlation with GAB renal clearance, since GAB is mainly eliminated by glomerular filtration. [18][19][20] However, studies suggested the activity of the organic cation transporters OCT2 and OCTN1 in the renal excretion of GAB.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, anticonvulsants such as Valproic acid, and Clonazepam are greater than 88% protein bound so they do not cross the blood brain barrier well and therefore provide little if any medication to the targeted areas. In addition, Valproic acid and similar drugs demonstrate serum protein saturable binding which can impact other medications when given simultaneously [62]. Newer anticonvulsants such as ethosuximide and topirimate are more promising, yet the disease is far from controlled.…”
Section: Clinical Relevance and Conclusionmentioning
confidence: 99%
“…9 Gabapentin has variable absorption and nonlinear pharmacokinetics, which leads to large interindividual differences in doseto-plasma concentrations and makes it an excellent candidate for therapeutic drug monitoring (TDM). 10,12 The interaction potential is therefore seen as low, even though interactions with some antacids and analgesics have been reported. 10,12 The interaction potential is therefore seen as low, even though interactions with some antacids and analgesics have been reported.…”
mentioning
confidence: 99%
“…7,10,11 It is not protein bound or metabolized, but rather cleared entirely by renal elimination, with an elimination half-life of 5-7 hours in healthy subjects. 10,12 The interaction potential is therefore seen as low, even though interactions with some antacids and analgesics have been reported. 13,14 Therapeutic drug monitoring is a commonly used tool to optimize treatment of epilepsy 7 and has been used as a part of the comprehensive care approach in epilepsy for 50 years.…”
mentioning
confidence: 99%